Cultural Identity of Football Supporter Community in Surabaya (Phenomenology Studies of Bonek Campus as a Supporter Community of Persebaya in Surabaya) - Ririn Puspita Tutiasri; Ade Kusuma (Nusantara Science and Technology Proceedings)
Cultural identity refers to the characteristics or sign possessed by a cultured group. Cultural identity will be attached to the identity of members of the cultural group. One of the cultural identity inherent in Surabaya is the term "Bonek". At first, the Bonek call was only intended for football supporter of Persebaya in Surabaya, but later it become the one of the stereotypes inherent in the people of Surabaya as a whole. Image of Bonek can not be separated from the abbreviation of the word itself, ie bondo nekat or it means dare to do anything to support them despite not having capital (material). Bonek appearance that tends to 'quirky' and not neatly also create a negative impression. Bonek also often reported getting into fight with other supporters, security apparatus, or journalists so that create a fanatical supporters image can not be separated by the riots that happen inside or outside the stadium. This prejudice will obviously disadvantageous to Surabaya supporters who are sportive and orderly when their support Persebaya Surabaya. Bonek Campus is one of the community of Persebaya Surabaya supporters who has been established since 2011. Their existence will give its own color to the diversity of football supporters in Surabaya, even Indonesia. For that the researcher is interested to conduct phenomenology study about Bonek Campus as a community of Persebaya supporters in Surabaya. Data collection through participatory observation, indepth interview, focus group discussion and literature study to explore more in depth how perception of Bonek Campus members to their role and function as football supporter community? Furthermore, researchers will identify how the cultural identity Bonek Campus as a community of football supporters Persebaya in Surabaya? Given the image of football supporters, especially Persebaya Surabaya is often considered arrogant, as do actions that result in fights and vandalism of public facilities.The output of this first phase of research is the data of Bonek Campus cultural identity as one of football supporter community in Surabaya. Further, the results will used as the basis of the preparation and development of the model of cultural identity learning as an effort to formation of Indonesian football supporters who have ethics and sportive.